Acute postoperative pain is an independent predictor of chronic postsurgical pain following total knee arthroplasty at 6 months: a prospective cohort study. Issue 3 (15th February 2019) - Buvanendran, Asokumar; Della Valle, Craig J; Kroin, Jeffrey S; Shah, Mahendra; Moric, Mario; Tuman, Kenneth J; McCarthy, Robert J
Abstract : Background: Approximately 15% of patients report persistent knee pain despite surgical success following total knee arthroplasty (TKA). The purpose of this study was to determine the association of acute-postsurgical pain (APSP) with chronic postsurgical pain (CPSP) 6 months after TKA controlling for patient, surgical and psychological confounding factors. Methods: Adult patients with osteoarthritis undergoing primary elective tricompartmental TKA, with the operated knee the primary source of preoperative pain, were studied between March 2011 and February 2017. Patients received standard operative management and a perioperative multimodal analgesia regimen. The primary outcome was CPSP at 6 months. The primary variable of interest was the APSP (weighted mean pain score) for 72 hours postoperatively. Patient, surgical and psychological confounders were assessed using binary logistic regression. Results: 245 cases were analyzed. The incidence of CPSP was 14% (95% CI 10% to 19%). Median APSP values were 4.2 (2.2–5.0) in the CPSP group and 2.8 (1.8–3.7) without CPSP, difference 1.4 (95% CI 0.1 to 1.8, p=0.005). The unadjusted odds for CPSP with an increase of 1 in APSP was 1.46 (95% CI 1.14 to 1.87, p=0.002)). After multivariable risk adjustment, the OR for CPSP for an increase of 1 in the APSP was 1.53 (95% CI 1.12 to 2.09, p=0.008). Conclusions: APSP is a risk factor for CPSP following TKA even after adjusting for confounding variables such as pain catastrophizing, anxiety, depression and functional status. Studies are needed to determine if APSP is a modifiable risk factor for the development of CPSP.